Digitizing the social contract: producing American political culture in the age of new media - Howard, P (Taylor and Francis, 2010)
Campaigns are complex exercises in the creation, transmission, and mutation of significant political symbols. However, there are important differences between political communication through new media and political communication through traditional media. I argue that the most interesting change in patterns of political communication is in the way political culture is produced, not in the way it is consumed. These changes are presented through the findings from systematic ethnographies of two organizations devoted to digitizing the social contract. DataBank.com is a private data mining company that used to offer its services to wealthier campaigns, but can now sell data to the smallest nascent grassroots movements and individuals. Astroturf-Lobby.org is a political action committee that helps lobbyists seek legislative relief to grievances by helping these groups find and mobilize their sympathetic publics. I analyze the range of new media tools for producing political culture, and with this ethnographic evidence build two theories about the role of new media in advanced democracies-a theory of thin citizenship and a theory about data shadows as a means of political representation.